Outcome of primary adult optical penetrating keratoplasty in a public health service facility of a developing country - Wagoner, Michael D. (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Surgical Sciences. Ophthalmology))--Stellenbosch University, 2008.